Rate and Causes of Conversion from Laparoscopic to Open Cholecystectomy among Iraqi Patients in Basrah-A Prospective Clinical Study - Haider Kadhim Abdulrazaaq Almohsin; Muntadher Muhamed Jawad; Luay Saddam Fahad Alhamd (Open Journal of Physicians and Surgeons, 2025)
Background: In recent years, advances in laparoscopic technologies have allowed the widespread introduction of laparoscopic cholecystectomy as a minimally invasive and safe procedure recognized as the "Gold Standard" worldwide. Nonetheless, conversion to laparotomy after laparoscopic surgery remains significant challenge to the surgeons and the conversion rates are widely varied among different centers. Objectives: To estimate the rate the main causes and predictors of conversion from laparoscopic to open cholecystectomy among Iraqi Patients in Basrah city. Patients and Methods: A cross-sectional study was conducted during a period of 32 months, from October 2022 to May 2025. The study included 428 patients presented with symptomatic cholelithiasis and met the inclusion criteria to whom elective laparoscopic cholecystectomy was performed. Results: Among the studied group, 15 (3.5%) patients needed laparotomy and converted to open cholecystectomy, the conversion rate was significantly higher (7.5%) in patients older than 50 years, male gender (6.8%), also it was higher in obese patients (9.3%), those with acute cholecystitis (11.3%), patients with prior abdominal surgeries (10.8%) and in those with gallbladder wall thickness of > 3 mm (8.9%). Dense adhesion was the stronger predictor for conversion with an odds ratio of 4.096, ((P. value<0.05). Conclusions: The overall rate of conversion from laparoscopic to open cholecystectomy among the studied group was 3.5%. The reported conversion rate in this study falls within the lower range of conversion rates reported globally. Dens adhesion was the stronger predictor of conversion from laparoscopic to open cholecystectomy followed by age older than 50 years, obesity, male gender, a gallbladder thickening of more than 3 mm, and acute type of cholecystitis